2019
DOI: 10.1017/s1366728919000695
|View full text |Cite
|
Sign up to set email alerts
|

Are similar control processes implemented during single and dual language production? Evidence from switching between speech registers and languages

Abstract: To investigate whether similar control processes are used during single and dual language production, we compared register switching (formal and informal speech in the same language) vs. language switching (French and English). The results across two experiments showed a positive correlation of overall register- and language-switch costs and similar formal French switch costs across the two switching tasks. However, whereas increasing the cue-to-stimulus interval resulted in a reduction of language-switch cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The long CSI used in the current study was longer than most studies that manipulated CSI length (e.g., [6,12,25,[33][34][35][36]), with the exception of Lavric et al [37] that used a long CSI of 1500ms. We chose to use no CSI, instead of a very short CSI (e.g., 100ms CSI), along the lines of previous studies [35,38], as this would provide a more extreme difference between CSI conditions (i.e., preparation vs. no preparation relative to more vs. less preparation).…”
Section: Methodsmentioning
confidence: 99%
“…The long CSI used in the current study was longer than most studies that manipulated CSI length (e.g., [6,12,25,[33][34][35][36]), with the exception of Lavric et al [37] that used a long CSI of 1500ms. We chose to use no CSI, instead of a very short CSI (e.g., 100ms CSI), along the lines of previous studies [35,38], as this would provide a more extreme difference between CSI conditions (i.e., preparation vs. no preparation relative to more vs. less preparation).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the possible language-specific control processes implemented during our task switching paradigm would be control processes implemented during single language processing, as participants were always using the same language in the task switching blocks. Previous studies investigating the control processes during single and mixed language processing have shown that they can be different (Abutalebi et al, 2008;Declerck et al, 2017;Declerck et al, 2020). So, comparing within-and between-language switch costs does not necessarily mean that the same control processes are used.…”
Section: Limitationsmentioning
confidence: 99%
“…Language switching costs are likely to persist even when speakers are given ample time to prepare (e.g., CSI up to 800 ms in Costa & Santesteban, 2004; Declerck, Ivanova, Grainger, & Duñabeitia, 2020; CSI up to 1000 ms in Philipp et al., 2007; CSI up to 1175 ms in Graham & Lavric, 2021; CSI up to 1500 ms in Fink & Goldrick, 2015; Verhoef et al., 2009), but also when the language to use next is predictable (i.e., when the same language sequence is used throughout a task such as in Declerck et al., 2015; Declerck, Philipp, & Koch, 2013; Festman, Rodriguez‐Fornells, & Münte, 2010; Jackson, Swainson, Cunnington, & Jackson, 2001; 2004) or when the speakers voluntarily switch language (e.g., de Bruin, Samuel, & Duñabeitia, 2018; Gollan & Ferreira, 2009; Gollan, Kleinman, & Wierenga, 2014; Gross & Kaushanskaya, 2015). Yet, a recent finding seems to challenge the hypothesis that speakers are unable to fully prepare for a language switch (Mosca & Clahsen, 2016).…”
Section: Introductionmentioning
confidence: 99%